Effects of a multicomponent physical activity promoting program on sedentary behavior, physical activity and body measures: a longitudinal study in different office types - Viktoria Wahlström; Frida Bergman; Fredrik Öhberg; Therese Eskilsson; Tommy Olsson; Lisbeth Slunga Järvholm (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVES: The aim of this study was to investigate effects of a multicomponent program promoting physical activity on sedentary behavior, physical activity, and body measures, when relocating from cell offices to either a flex or cell office. METHODS: The Active Office Design (AOD) study is a longitudinal non-randomized controlled study performed in a municipality in northern Sweden. A subsample of 86 participants were randomly recruited from the AOD study to objectively measure sedentary behavior and physical activity, using ActivPAL and ActiGraph, before and after relocation to the two different office types. The multicomponent program promoting physical activity was performed in both offices. Data were analyzed using linear mixed models. RESULTS: Eighteen months after relocation, the total number of steps per work day increased by 21% in the flex office and 3% in the cell office group, compared to baseline. Moderate and vigorous physical activity (MVPA) during work hours increased by 42% in the flex office group and 19% in the cell office group. No changes were seen regarding sitting time at work. Small additive effects for walking and MVPA were seen for both groups during non-work time. Weight increased in the flex office group. CONCLUSIONS: This long-term study shows that a multicomponent workplace intervention can lead to increased walking time, steps, and MVPA in a flex compared to a cell office. Small additive increases of physical activity were seen during non-work time in both groups. More long-term controlled studies are needed to confirm these results.